Flexural Strengthening of RC Beams with NSM-CFRP: A Review on the Role of Concrete Strength and Strip Layout - Nadila, Sifa Ulhaq; Gunadi, Riawan (Jurnal Teknik Sipil, 2025)
Reinforced Concrete (RC) beams are primary structural elements that often suffer damage due to repeated loading, particularly in flexural cracks that propagate and reduce structural integrity and load-carrying capacity. Conventional repair methods are considered inefficient due to their high cost, complexity, and time-consuming procedures. As a viable alternative, composite materials like Carbon Fiber Reinforced Polymer (CFRP) have gained attention due to their superior tensile strength, lightweight properties, Corrosion resistance, and Straightforward application. This research highlights evaluating the performance of the Near-Surface Mounted (NSM) technique with CFRP in improving the bending strength of reinforced concrete beams. Two specimens were experimentally tested, each incorporating concrete with compressive capacities of 32 MPa and 35 MPa, using configurations of one and two CFRP strips. The experimental results indicated that the use of two CFRP strips led to an enhancement in load-carrying capacity by as much as 35,67%. Additionally, improvements in ductility and more controlled failure modes were observed. This study confirms that the NSM-CFRP system is highly effective as a structural strengthening solution, particularly for elements requiring high flexural performance.